2019
DOI: 10.1016/j.ejogrb.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the value of intrapartum fetal scalp blood sampling to predict adverse neonatal outcomes: A UK multicentre observational study

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Not only the physiological and scientific basis of FBS has been recently questioned [28,29], the recent Cochrane Systematic Review has suggested that the use of fetal scalp blood sampling does not improve perinatal outcomes [30]. A recent prospective multicenter trial from 44 maternity units in the UK has also reported that FBS did not improve perinatal outcomes and increased intrapartum operative interventions by 60% [31]. The "Achilles Heel" of the STAN technology is the misinterpretation of the CTG trace due to inter and intra-observer variability as a result of using guidelines which are based on "pattern recognition" on all human fetuses with different individual physiological reserves.…”
Section: Are Our Results Reproducible?mentioning
confidence: 99%
“…Not only the physiological and scientific basis of FBS has been recently questioned [28,29], the recent Cochrane Systematic Review has suggested that the use of fetal scalp blood sampling does not improve perinatal outcomes [30]. A recent prospective multicenter trial from 44 maternity units in the UK has also reported that FBS did not improve perinatal outcomes and increased intrapartum operative interventions by 60% [31]. The "Achilles Heel" of the STAN technology is the misinterpretation of the CTG trace due to inter and intra-observer variability as a result of using guidelines which are based on "pattern recognition" on all human fetuses with different individual physiological reserves.…”
Section: Are Our Results Reproducible?mentioning
confidence: 99%
“…Recently, a large observational study of FBS from 44 maternity units in the UK was published [25]. The conclusion of the study results was that FBS as an adjunct tool to cardiotocography, offered limited value to predict neonatal acidaemia, low Apgar Scores, and admission to NICU.…”
Section: Discussionmentioning
confidence: 99%
“…This was evident almost immediately by complete cessation of the fetal scalp blood sampling (FBS) for "pathological" CTG traces by obstetricians of all grades, from approximately 12-15% earlier (i.e., 500-700 per year). Cochrane Systematic Reviews had repeatedly concluded that the use of fetal blood sampling (FBS) during labor (both fetal scalp lactate and pH) did not appear to influence any long-term neonatal outcomes or reduce intrapartum interventions [18,19], and scientific studies have shown that the use of FBS may in fact significantly increase the rate of emergency caesarean sections [20,21], and its anatomical, physiological, and scientific basis has been repetitively questioned recently [22][23][24][25]. Moreover, FBS has been found to be of limited value in the presence of meconium (i.e., bile acids would change the pH) [26], and contamination with the amniotic fluid (alkaline pH of the amniotic fluid would neutralize the acidic pH of the scalp sample leading to a false reassurance) resulting in poor perinatal outcomes [23][24][25]27].…”
Section: What Is the Impact Of Implementing Physiological Interpretation Of Ctg?mentioning
confidence: 99%